Meat quality of swine supplemented with ractopamine under commercial conditions in Brazil - Athayde, N. B. [UNESP]; Dalla Costa, O. A.; Roça, Roberto de Oliveira [UNESP]; Guidoni, A. L.; Ludtke, C. B.; Lima, G. J. M. M. (Amer Soc Animal Science, 2012)
Commercial crossbred barrows and gilts (n = 340) were used to study the effects of different dietary inclusions of ractopamine hydrochloride (RAC) on quality of LM and semimembranosus muscle (SM). Pigs were blocked by BW (107.3 +/- 0.76 kg) and allotted to gender-specific pens (10 to 12 pigs/pen), and within blocks, pens of barrows or gilts (10 pens/treatment) were randomly assigned to 1 of 3 dietary RAC inclusions (0, 5, or 10 mg/kg) fed during the last 28 d before slaughter. Initial (45-min) and ultimate (24-h) pH and temperature were measured in LM and SM. Visual and instrumental [lightness (L*), redness (a*), and yellowness (b*) values] color as well as drip loss percentages were measured in both muscles after the 24-h chilling period at 1 to 4 degrees C. The LM was also evaluated for marbling, and samples of the LM were used to measure intramuscular fat (IMF) content, cooking losses, and Warner-Bratzler shear force (WBSF). Pork quality characteristics of the LM (P >= 0.227) and SM (P >= 0.082) did not differ between barrows and gilts. Furthermore, neither pH nor temperature of the LM (P >= 0.164) or SM (P >= 0.284) was affected by feeding pigs RAC. The LM from pigs fed 10 mg/kg of RAC received lesser (P = 0.032) subjective color scores than LM from pigs fed 0 and 5 mg/kg of RAC, and LM from pigs fed 10 mg/kg of RAC was less (P = 0.037) red than LM from pigs fed 0 mg/kg of RAC. In addition, SM from pigs fed 10 mg/kg of RAC had lesser (P <= 0.015) a* and b* values than pork from control-fed pigs; however, L* values for LM and SM were not (P >= 0.081) affected by dietary RAC. Drip loss percentages of the LM were similar (P = 0.815) among RAC treatments, but the SM from RAC-fed pigs had smaller (P = 0.020) drip loss percentages than SM from pigs fed 0 mg/kg of RAC. Marbling scores and IMF content of the LM did not (P >= 0.133) differ among RAC treatments; however, WBSF values were greater (P = 0.005) for LM chops from pigs fed 10 mg/kg than chops from pigs fed 0 and 5 mg/kg of RAC. Even though feeding barrows and gilts 10 mg/kg of dietary RAC reduced (P = 0.050) cooking losses of LM chops compared with feeding 5 mg/kg of RAC, including 10 mg/kg of RAC in the diet of finishing pigs reduced pork tenderness. Therefore, results from this study support the recommendation that including 5 mg/kg of RAC in finishing diets should improve live pig performance without detrimental effects on fresh pork quality and cooked pork palatability.
Keywords: beta-adrenergic agonist; color; drip loss; pH; pork